Alloy, aggregate of alloy nanoparticles, and catalyst

Alloys with a standard deviation of 15 atomic % or less ensure high uniformity of solid solution, addressing non-uniformity issues in existing alloys, enhancing stability and durability for high-temperature catalyst applications.

JP2024178229APending Publication Date: 2024-12-24KYOTO UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024157491
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-07-06
Filing Date
2024-09-11
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing alloys and high-entropy alloy nanoparticles suffer from non-uniformity of solid solution, leading to phase separation and reduced stability under high temperatures, which affects their performance and lifespan as catalysts.

Method used

Development of alloys composed of three or more elements with a standard deviation of element distribution within the alloy of 15 atomic % or less, ensuring high uniformity of solid solution, confirmed by STEM-EDS analysis.

Benefits of technology

The novel alloys exhibit enhanced compositional stability and durability, maintaining high material homogeneity even at elevated temperatures, suitable for long-term use as catalysts in chemical reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178229000026
    Figure 2024178229000026
  • Figure 2024178229000027
    Figure 2024178229000027
  • Figure 2024178229000028
    Figure 2024178229000028
Patent Text Reader

Abstract

To provide a novel alloy composed of three or more elements, exhibiting high solid solution uniformity.SOLUTION: The present invention provides a novel alloy composed of three or more elements, wherein all the standard deviations of distribution in the alloy of each element constituting the alloy are 15 atom% or less. The alloy exhibits high solid solution uniformity.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alloy, an aggregate of alloy nanoparticles, and a catalyst, and in particular to a novel alloy or aggregate of alloy nanoparticles that is composed of three or more elements and has high uniformity in solid solution, and to a catalyst that contains the alloy or aggregate of alloy nanoparticles. [Background technology]

[0002] Alloys in which metal elements that are not mixed at the atomic level are dissolved in a solid solution, and high-entropy alloy nanoparticles are known (see Patent Document 1 and Non-Patent Documents 1 to 4).

[0003] Patent Document 1 describes that by adding a third element M (M=at least one of Rh, Ir, Au, Ag, and Pt) to PdRu to form multi-element solid solution alloy fine particles, catalytic performance can be maintained even when used at high temperatures for a long period of time. Patent Document 1 does not specify the uniformity of the alloy solid solution (or mixture).

[0004] Non-Patent Document 1 describes a method for producing high-entropy alloy nanoparticles in which five or more types of metal salts are supported on a carbon material (carbon nanofiber), a large current is applied to the material, and the material is rapidly heated to a high temperature of 2000 K or higher and then rapidly cooled. The right column on page 3 of Non-Patent Document 1 describes that the variation in element composition in five-kind mixture PtPdCoNiFe is about 10%, which is smaller than the variation in lithography methods, which exceeds 50%.

[0005] Non-Patent Document 2 describes a manufacturing method in which a graphene support and a metal are mechanically pulverized to form high-entropy alloy nanoparticles on the graphene support. The elemental composition of the FeCrCoCuNi nanoparticles shown in Fig. 9 did not show a uniform mixture.

[0006] Non-Patent Document 3 describes a manufacturing method for obtaining nanoparticles by irradiating a laser on a target of a bulk high-entropy alloy of 3d transition metals (fourth period). Table 2 lists the composition of CoCrFeMnNi nanoparticles, but does not show the uniformity of the mixture.

[0007] Non-Patent Document 4 describes a manufacturing method for obtaining nanoparticles by solvothermal synthesis at about 200°C using organometallic salts of platinum group elements. Fig. 5 shows scanning transmission electron microscope (STEM)-energy dispersive X-ray analysis (EDS, also known as EDX) images of PtRhRu and PtPdIrRhRu particles, but the uniformity of the mixture at the atomic level could not be read from the images. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] WO2017 / 150596 [Non-patent literature]

[0009] [Non-Patent Document 1] Science (2018) 359, 1489-1494 [Non-Patent Document 2] SCIENTIFIC REPORTS (2018) 8:8737 [Non-Patent Document 3] RSC Adv. (2019) 9, 18547-18558 [Non-Patent Document 4] Adv.Funct.Mater. (2019) 1905933 Summary of the Invention [Problem to be solved by the invention]

[0010] In the lower left part of page 6 of Non-Patent Document 4, it is stated that the obtained nanoparticles are stable up to 700K (427℃). In particular, an XRD pattern corresponding to hcp appears from 800K, which suggests that a hcp Ru-rich phase has appeared. On the other hand, it is stated that the positions of the fcc peaks remain almost unchanged. If a uniform alloy is formed at first and Ru is mainly precipitated, as shown in Table S1, the atomic radius of Ru is smaller than the others, so its lattice constant expands according to Beggars' law. In addition, Fig. S16 shows the relationship between melting point and crystallite size, and Ru is a single metal and is 2nm or less. From these, Non-Patent Document 4 handles that an fcc alloy with large crystallites and small Ru-rich particles are precipitated unevenly at first, but due to the small size of the crystals, a uniform fcc alloy is formed by XRD. When the nanoparticles are heated, the small hcp particles become coarse and a prominent peak appears in the XRD, but since the peak position of the fcc does not change, it is thought that there is almost no change in the metal composition ratio (Ru does not precipitate from the alloy and exists as a separate particle). In other words, it is thought that the nanoparticles obtained in Non-Patent Document 4 are not uniformly mixed. In the case of solvothermal synthesis, the sealed vial is gradually heated, so that metals that are easily decomposed or reduced react gradually, and since the reduction rate differs for each metal, it is thought that it is difficult to produce a uniform alloy.

[0011] As described above, there is room for improvement in the uniformity of the solid solution in alloys containing metal elements that cannot be mixed at the atomic level, and in high-entropy alloy nanoparticles. The problem to be solved by the present invention is to provide a novel alloy which is composed of three or more elements and has high uniformity in solid solution. [Means for solving the problem]

[0012] In the present invention, we have found a new alloy with a remarkably high level of uniformity in the solid solution, which has never been known before, and have solved the above-mentioned problems. When viewed macroscopically as a block (bulk) or an aggregate of particles (powder), such an alloy has the same average composition as conventional alloys, but is a new alloy with completely different physical properties in that it has a high level of uniformity in the solid solution. The configuration of the present invention, which is a specific means for solving the above problems, and a preferred configuration of the present invention will be described below.

[0013] [1] An alloy consisting of three or more elements, An alloy in which the standard deviation of the distribution of each of the elements that make up the alloy is 15 atomic % or less. [2] The alloy according to [1], wherein the correlation coefficients of the distributions of the two elements constituting the alloy are both within ±0.50. [3] An alloy according to [1] or [2], wherein the elements constituting the alloy include a combination of elements that are not solid-soluble in a phase equilibrium diagram. [4] The alloy according to any one of [1] to [3], wherein the elements constituting the alloy include at least three elements selected from the group consisting of platinum group metals (Ru, Rh, Pd, Os, Ir, Pt), Ag, Au, Cd, Hg, In, Tl, Sn, Pb, Sb, Bi, Mo, W, Tc, Re, 3d metals (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), Ga, Ge, As, H, B, Al, C, Si, N, P, Y, Zr, Nb, lanthanides, Hf, and Ta. [5] The alloy according to any one of [1] to [4], wherein the elements constituting the alloy include at least one selected from the group consisting of Ru, Rh, Pd, Os, Ir, Pt, Ag, Au, and Ni. [6] The alloy contains m elements, where m is an integer of 3 or more. For each element i constituting the alloy, where i is an integer between 1 and m, the average composition in the alloy is C i In atomic percent, The standard deviation of the distribution of each element in the alloy is expressed by the following formula 1: i Using 2.5×s i The alloy according to any one of [1] to [5], wherein the content is 0.05 atomic % or less.

number

[10] The alloy according to [8], wherein the nanoparticles are supported on a support.

[11] The alloy according to

[10] , wherein the support is a non-carbon material support or a particulate carbon support.

[12] An aggregate of alloy nanoparticles containing 98% or more by number of the alloy described in [8].

[13] A catalyst comprising the alloy according to any one of [1] to

[11] or an aggregate of alloy nanoparticles according to

[12] . Effect of the Invention

[0014] According to the present invention, it is possible to provide a novel alloy which is composed of three or more elements and has a high degree of uniformity in the solid solution. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a scanning transmission electron microscope photograph used in the EDS line analysis of the STEM-EDS of the alloy obtained in Example 1. [Diagram 2] Figure 2(A) is a graph showing the characteristic X-ray counts at each position (distance from the 0.00 nm position; the same applies to the following graphs) in the arrowed portion of Figure 1. Figure 2(B) is a graph showing the composition at each position in the arrowed portion of Figure 1. [Diagram 3]FIG. 3 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Example 1. [Figure 4] Fig. 4(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 3. Fig. 4(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 3. [Diagram 5] FIG. 5 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Example 1. [Figure 6] Fig. 6(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 5. Fig. 6(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 5. [Figure 7] FIG. 7 shows a high-angle annular dark field (HAADF) STEM image and an energy dispersive X-ray analysis (EDS) map of the alloy obtained in Example 1. [Figure 8] FIG. 8 is an energetic powder X-ray diffraction (XRD or PXRD) pattern of the alloy obtained in Example 1. [Figure 9] FIG. 9 is a transmission electron microscope (TEM) photograph of the alloy obtained in Example 1. [Figure 10] Fig. 10(A) is a graph showing the hydrogen evolution reaction (HER) catalytic activity of the alloy obtained in Example 1. Fig. 10(B) is a graph showing a comparison of the HER catalytic activity of the alloy obtained in Example 1 measured three times. [Figure 11] FIG. 11 is a scanning transmission electron microscope photograph used in the EDS line analysis of the STEM-EDS of the alloy obtained in Example 11. [Figure 12] Fig. 12(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 11. Fig. 12(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 11. [Figure 13]FIG. 13 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Example 11. [Figure 14] Fig. 14(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 13. Fig. 14(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 13. [Figure 15] FIG. 15 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Example 11. [Figure 16] Fig. 16(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 15. Fig. 16(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 15. [Figure 17] FIG. 17 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Example 11. [Figure 18] Fig. 18(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 17. Fig. 18(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 17. [Figure 19] FIG. 19 shows an HAADF-STEM image and an energy dispersive X-ray analysis (EDS) map of the alloy obtained in Example 11. [Figure 20] FIG. 20 is an energetic powder X-ray diffraction (XRD or PXRD) pattern of the alloy obtained in Example 11. [Figure 21] FIG. 21 is a transmission electron microscope (TEM) photograph of the alloy obtained in Example 11. [Figure 22] Figure 22(A) is a graph showing the HER catalytic activity of the alloy obtained in Example 11. Figure 22(B) is a graph showing a comparison of the HER catalytic activity of the alloy obtained in Example 11 measured three times. [Diagram 23] FIG. 23 is a scanning transmission electron microscope photograph used in the EDS line analysis of the STEM-EDS of the alloy obtained in Example 21. [Figure 24]Fig. 24(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 23. Fig. 24(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 23. [Diagram 25] FIG. 25 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Example 21. [Figure 26] Fig. 26(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 25. Fig. 26(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 25. [Figure 27] FIG. 27 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Example 21. [Figure 28] Fig. 28(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 27. Fig. 28(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 27. [Figure 29] FIG. 29 is a scanning transmission electron microscope photograph used in the STEM-EDS EDS line analysis of the alloy obtained in Example 22. [Diagram 30] Fig. 30(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 29. Fig. 30(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 29. [Diagram 31] FIG. 31 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Example 22. [Diagram 32] Fig. 32(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 31. Fig. 32(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 31. [Diagram 33] FIG. 33 shows an HAADF-STEM image and an energy dispersive X-ray analysis (EDS) map of the alloy obtained in Example 21. [Diagram 34]FIG. 34 shows an HAADF-STEM image and an energy dispersive X-ray analysis (EDS) map of the alloy obtained in Example 22. [Diagram 35] FIG. 35 is an energetic powder X-ray diffraction (XRD or PXRD) pattern of the alloys obtained in Examples 21 and 22. [Diagram 36] Fig. 36(A) is a transmission electron microscope (TEM) image of the alloy obtained in Example 21. Fig. 36(B) is a transmission electron microscope (TEM) image of the alloy obtained in Example 22. [Figure 37] FIG. 37 is a graph showing the HER catalytic activity of the alloys obtained in Examples 21 and 22. [Figure 38] FIG. 38 shows an HAADF-STEM image and an energy dispersive X-ray analysis (EDS) map of the alloy obtained in Example 31. [Figure 39] FIG. 39 shows an HAADF-STEM image and an electron energy loss spectroscopy (EELS) map of the alloy obtained in Example 31. [Diagram 40] FIG. 40 is an energetic powder X-ray diffraction (XRD or PXRD) pattern of the alloy obtained in Example 31. [Diagram 41] 41(A) is a transmission electron microscope (TEM) image of the alloy obtained in Example 31. FIG. 41(B) is a transmission electron microscope (TEM) image of PdRu used as a raw material in Example 31. [Diagram 42] FIG. 42 is a scanning transmission electron microscope photograph used in the STEM-EDS EDS line analysis of the alloy obtained in Example 41. [Diagram 43] Fig. 43(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 42. Fig. 43(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 42. [Diagram 44] FIG. 44 is a scanning transmission electron microscope photograph used in the STEM-EDS EDS line analysis of the alloy obtained in Comparative Example 42. [Diagram 45]Fig. 45(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 44. Fig. 45(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 44. [Figure 46] FIG. 46 is a scanning transmission electron microscope photograph used in another EDS line analysis of STEM-EDS of the alloy obtained in Comparative Example 42. [Figure 47] Fig. 47(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 46. Fig. 47(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 46. [Figure 48] FIG. 48 is a scanning transmission electron microscope photograph used in the STEM-EDS EDS line analysis of the alloy obtained in Example 51. [Figure 49] Fig. 49(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 48. Fig. 49(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 48. [Figure 50] FIG. 50 is a scanning transmission electron microscope photograph used in the STEM-EDS EDS line analysis of the alloy obtained in Example 61. [Figure 51] Fig. 51(A) is a graph showing the characteristic X-ray counts at each position in the portion indicated by the arrow in Fig. 50. Fig. 51(B) is a graph showing the composition at each position in the portion indicated by the arrow in Fig. 50. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below. The following description of the constituent elements may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "~" means a range including the numerical values ​​before and after "~" as the lower and upper limits.

[0017] [alloy] The alloy of the present invention is an alloy composed of three or more elements, and the standard deviation of the distribution of each of the elements constituting the alloy within the alloy is 15 atomic % or less. This structure makes it possible to provide a novel alloy that is composed of three or more elements and has high uniformity of the solid solution. The uniformity of the solid solution of an alloy is a measure of the state of the solid solution, that is, how uniform the composition distribution of the solid solution is. Conventionally, alloys consisting of multiple insoluble elements may gradually develop a bias in metal distribution over time, and may eventually cause phase separation. Alloys with low uniformity of solid solution and a standard deviation exceeding the upper limit of the range specified in this specification may gradually develop a bias in metal distribution over time and may eventually cause phase separation, and may have inferior catalytic performance compared to the alloy of the present invention, and may be short-lived or unstable when used in an environment exposed to high temperatures for a long time. In contrast, the alloy of the present invention is highly homogenized, and therefore has excellent compositional stability and is less susceptible to phase separation. Therefore, the alloy of the present invention is suitable for applications requiring high durability, such as chemical reaction catalysts, in which the alloy is exposed to high temperatures for long periods of time. In other words, the alloy of the present invention can be used to produce a catalyst with a long life. It is more preferable that the alloy shows a stable structure when heated and has high material uniformity. In particular, in a high-entropy alloy of five or more elements, the entropy S of the configuration is large, and therefore a uniform solid solution phase is stable at high temperatures due to the Gibbs free energy G=H-TS (where H is enthalpy, T is absolute temperature, and S is entropy). It is particularly preferable that the alloy shows a stable structure and has high material uniformity when heated, for example, to 500K or higher (preferably 700K or higher, more preferably 900K or higher). The material uniformity can be confirmed by in situ XRD or STEM-EDS. In addition, it is preferable that the alloy has constituent elements mixed at the atomic level. Specifically, when the alloy is used as an assembly of alloy nanoparticles, it is preferable that the assembly of alloy nanoparticles contains the alloy of the present invention at 98% by number or more. Alternatively, it is preferable that any alloy nanoparticle constituting the assembly of alloy nanoparticles contains all of three or more elements as constituent elements. In addition, when the alloy is used as a catalyst containing a large number of alloy nanoparticles, it is preferable that the alloy nanoparticles contained in the catalyst contain 98% by number or more of the alloy nanoparticles of the present invention. Alternatively, it is preferable that any alloy nanoparticles contained in the catalyst contain all of three or more elements as constituent elements. Preferred embodiments of the present invention will now be described.

[0018] <Element> The alloy of the present invention is composed of three or more elements, preferably composed of 3 to 50 elements, more preferably composed of 3 to 25 elements, particularly preferably composed of 3 to 10 elements, more particularly preferably composed of 3 to 5 elements, and even more particularly preferably composed of 3 or 4 elements.

[0019] There is no particular limitation on the types of elements constituting the alloy of the present invention. The elements constituting the alloy may include a combination of elements that are not solid-soluble in the phase equilibrium diagram, or may not include a combination of elements that are not solid-soluble in the phase equilibrium diagram. That is, the alloy may be a combination of elements that cannot easily form a solid solution, or may be a combination of elements that can easily form a solid solution. Phase equilibrium diagrams are also called phase diagrams, state diagrams, alloy phase diagrams, etc., and all diagrams similar to these can be used as phase equilibrium diagrams in this specification. The phase equilibrium diagram may be a phase equilibrium diagram of two elements or a phase equilibrium diagram of three or more elements.

[0020] According to the present invention, a novel alloy having high uniformity of solid solution can be provided by using a wide variety of elements. Therefore, it is preferable that the elements constituting the alloy include a combination of elements that do not form a solid solution in a phase equilibrium diagram. In a phase equilibrium diagram, a combination of elements that does not form a solid solution is a combination that has an immiscible region of 30 atomic % or more at 1000°C and a pressure of 1 atm (normal pressure). It is more preferable that the elements constituting the alloy include a combination of elements that are not dissolved in a binary or ternary phase equilibrium diagram, and it is particularly preferable that the elements constituting the alloy include a combination of elements that are not dissolved in a binary or ternary phase equilibrium diagram. Among the combinations of two elements constituting the alloy, it is preferable to include a combination of elements that are not dissolved in at least one binary phase equilibrium diagram, and it is more preferable to include a combination of elements that are not dissolved in two or more binary phase equilibrium diagrams.

[0021] Among the combinations of two elements constituting the alloy, the combinations of elements that are not solid-soluble in at least one set of binary phase equilibrium diagrams include PdRu, AuIr, AgRh, AuRh, AuRu, CuRu, CuIr, AgCu, FeCu, AgIr, AgRu, MoRu, RhC, RuN, RuSn, PdOs, CuOs, AgOs, AuOs, CuRh, IrRh, IrPd, AgPt, AuPt, and other combinations of precious metals and most non-precious metals. Among the three or more elements constituting the alloy, the combinations of two elements that are not solid-soluble in a binary phase equilibrium diagram include PdRuB, AuRuIr, RuRhAu, PtIrRu, FeRuRh, AuIrRh, AgIrRh, AuPdRu, etc. Among the five or more elements that compose the alloy, examples of alloy nanoparticles that contain a combination of two elements that do not form a solid solution in a binary phase equilibrium diagram include the combination of PdRuRhOsIr and Pt, the combination of RuRhPdIr and Pt, and AuRuRhIrPt. Among the three combinations of elements constituting the alloy, combinations of elements that do not form a solid solution in at least one ternary phase equilibrium diagram include PdRuB, AuRuIr, RuRhAu, PtIrRu, FeRuRh, AuIrRh, AgIrRh, and AuPdRu. Even for combinations of elements for which no binary phase equilibrium diagram is known, if there is a region of immiscibility of 30 atomic % or more at 1000 °C and 1 atm pressure, it is included in the combinations of elements that are not dissolved in a phase equilibrium diagram.

[0022] It is preferable that the alloy contains an oxidation-resistant metal as an element that constitutes the alloy. An oxidation-resistant metal is a metal that maintains a metallic state (where the metallic structure, such as fcc, bcc, or hcp, can be confirmed) with a particle size of 50 nm or less, such as precious metals and Ni.

[0023] The alloy of the present invention preferably contains at least three elements selected from the group consisting of the platinum group (Ru, Rh, Pd, Os, Ir, Pt), Ag, Au, Cd, Hg, In, Tl, Sn, Pb, Sb, Bi, Mo, W, Tc, Re, the 3d metals (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), Ga, Ge, As, H, B, Al, C, Si, N, P, Y, Zr, Nb, the lanthanides, Hf, and Ta. It is more preferable that the elements constituting the alloy include at least three elements selected from the group consisting of platinum group (Ru, Rh, Pd, Os, Ir, Pt), Ag, Au, Cd, Hg, In, Tl, Sn, Pb, Sb, Bi, Mo, W, Tc, Re, 3d metals (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), Ga, Ge, As, B, Al, C, Si, N, P, and lanthanides. Among these, it is particularly preferable that the elements constituting the alloy include three elements selected from the group consisting of the platinum group (Ru, Rh, Pd, Os, Ir, Pt), Ag, Au, In, Tl, Sn, Mo, W, Re, the 3d metals (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), B, C, N, and lanthanides. It is particularly preferable that the elements constituting the alloy include at least three elements selected from the group consisting of Ru, Rh, Ir, Pt, Au, Ag, Sn, Cu, Mo, W, Re, Fe, Co, Ni, B, and N.

[0024] On the other hand, the elements constituting the alloy preferably include at least one of the group consisting of the platinum group metals (Ru, Rh, Pd, Os, Ir, Pt), Ag, Au, and Ni, and more preferably include two of them. Also, it is particularly preferable that the alloy includes at least one of the group consisting of Ru, Rh, Ir, Pt, Ag, Au, and Ni, and more particularly preferable that the alloy includes two of them.

[0025] The crystal structure of the alloy is not particularly limited. Depending on the composition of the alloy and the average number of valence electrons in the whole, the alloy may have a crystal structure such as fcc (face-centered cubic lattice), hcp (hexagonal close-packed lattice), bcc (body-centered cubic lattice), etc. In one preferred embodiment of the present invention, the alloy (particles) is a solid solution of fcc structure or hcp structure. However, when the alloy becomes an ordered alloy (i.e., has an ordered phase), forms an amorphous structure, or forms an intermetallic compound, structures other than those mentioned above can be maintained. When elements with significantly different atomic radii or electronegativity are mixed, an intermetallic compound may be formed. In the case of an intermetallic compound, the atomic arrangement is not random, but the alloy becomes an ordered alloy. Examples of combinations of two types of elements that make up the alloy include RhC, PdB, a combination of a noble metal and a transition metal, and a combination of a noble metal and a typical metal, such as RuSn. However, in the case of an ordered alloy with many constituent elements, the atomic sites in the ordered alloy may be randomly composed of specific multiple elements. For example, elements with large atomic radii may be randomly arranged at the atomic sites of elements with large atomic radii, and elements with small atomic radii may be randomly arranged at the atomic sites of elements with small atomic radii. Among the six elements of the platinum group, four elements are fcc (face-centered cubic lattice), namely Rh, Pd, Ir, and Pt, and two elements are hcp (hexagonal close-packed lattice), namely Os and Ru. The alloy (particle) of one preferred embodiment of the present invention is a solid solution of fcc structure containing an element of the platinum group. The alloy of another preferred embodiment of the present invention is a solid solution of hcp structure containing an element of the platinum group. Even when the six elements of the platinum group are used, the proportion of the fcc structure may be high as in the original proportion, or the proportion of the hcp structure may be high.

[0026] Since the alloy of the present invention has high uniformity of solid solution, it is preferable that three or more elements are uniformly distributed and solid-dissolved. Here, "uniformly distributed" means that there is no bias in the distribution of three or more elements, and that the standard deviation of the distribution of each element constituting the alloy within the alloy is a specific value or less (for example, 15 atomic % or less). Furthermore, it is preferable to be able to confirm that there is no bias in the distribution of each element (atom) by energy dispersive X-ray analysis (EDS) map. It is also preferable to be able to confirm a single fcc, bcc or hcp pattern by powder X-ray diffraction (XRD). For example, even if fcc and hcp coexist, if the interatomic distances of both structures are equal, the constituent elements are considered to be uniformly distributed in each structure. At that time, the metal composition of both fcc and hcp structures is equivalent, so the interatomic distances are equal to each other.

[0027] (Element ratio) In the alloy of the present invention, there is no particular restriction on the ratio of each element constituting the alloy (also referred to as the composition ratio) in the alloy, that is, there is no particular restriction on the average composition of the alloy of the present invention. In a preferred embodiment of the present invention, the upper limit of the percentage of the most abundant element, when the entire alloy is taken as 100 atomic %, is 99.9 atomic % or less, 80 atomic % or less, 70 atomic % or less, 60 atomic % or less, 50 atomic % or less, 45 atomic % or less, 40 atomic % or less, or 35 atomic % or less. The lower limit of the proportion of the smallest element when the entire alloy is taken as 100 atomic % is 0.1 atomic % or more, 1 atomic % or more, 5 atomic % or more, 9 atomic % or more, 10 atomic % or more, or 15 atomic % or more. Furthermore, the element with the highest atomic ratio is preferably 1 to 500 times, more preferably 1 to 5 times, even more preferably 1 to 3 times, particularly preferably 1 to 2 times, and most preferably 1 to 1.5 times that of the element with the lowest atomic ratio. When the alloy of the present invention is a high-entropy solid solution alloy, it is preferable that the atomic ratios of three or more elements are as close as possible.

[0028] <Standard deviation of distribution> In the alloy of the present invention, the standard deviation of the distribution of each element constituting the alloy within the alloy is 15 atomic % or less, more preferably 14 atomic % or less, particularly preferably 13 atomic % or less, more particularly preferably 12 atomic % or less, even more preferably 11 atomic % or less, even more preferably 10 atomic % or less, and even more particularly preferably 8.7 atomic % or less. Also, the standard deviation of the distribution of at least two elements constituting the alloy within the alloy is 15 atomic % or less, more preferably 14 atomic % or less, particularly preferably 13 atomic % or less, more particularly preferably 12 atomic % or less, even more preferably 11 atomic % or less, even more preferably 10 atomic % or less, and even more particularly preferably 8.7 atomic % or less. It is preferable that the standard deviation of the distribution of each element constituting the alloy within the alloy is 50% or less of the composition proportion of that element within the alloy, more preferably 40% or less, particularly preferably 30% or less, and even more particularly preferably 20% or less.

[0029] As the number of types of elements constituting the alloy increases, it is preferable that the standard deviation of the distribution of each element constituting the alloy within the alloy be in a lower range. When the alloy contains three types of elements, it is preferable that the standard deviation is within the above range. Consider the case where a random alloy with m elements is divided into a small volume and the spatial distribution is statistically analyzed. The average composition of the alloy is (C1, C2, . . . , C m ) atomic %, and the total number of atoms contained in the microspace (the number of atoms per microvolume being measured) is N, the statistical distribution of the number of atoms of each element contained in each microvolume can be approximated by a multinomial distribution in the case of a random alloy. In this case, the fluctuation in composition can be evaluated by the standard deviation, which is the spread of the distribution. The standard deviation s for each element i in the composition distribution of the microvolume is i (The standard deviation for each element i in the composition distribution in the measured microvolume) can be expressed by the following formula 1.

number

[0030] The standard deviation of the distribution of each element constituting the alloy within the alloy can be determined by the following method using STEM-EDS analysis. Elemental analysis is performed by line scan using multiple fields of view of a scanning transmission electron microscope. It is preferable to select a field of view in which many particles exist, and select particles that are at a moderate distance from the surrounding particles, do not overlap with each other, and have an average particle size. Dispersion, etc. may be the average of data calculated from multiple measurement points. Size dependency may also be examined and used as an average value, but an average size is used (can be used) as a representative point. The particle used as the representative point is the particle that is closest to the composition calculated by elemental analysis using XRF after calculating the average composition at each measurement point calculated from multiple measurement points, or the particle that is closest to the composition of each element in the mixed solution in which the raw material solutions are mixed. The analysis method of line analysis is to select one or more particles in the field of view of a specific measurement point and analyze them in the direction of the arrow, but almost the same results are obtained even if one or more other particles are arbitrarily selected and analyzed, and the same quality is obtained even if the direction of the arrow, the shape of the particle, and the particle size are different. Therefore, it is considered that almost the same results can be obtained for any alloy nanoparticle that constitutes an aggregate. In a certain field of view, the range (position range) for line analysis is adjusted for a range longer than the particle diameter of the alloy (e.g., the shape of nanoparticles). The range for line analysis is preferably a range that crosses the entirety of one or more selected particles, from the viewpoint of confirming uniformity throughout the particle. In other words, it is preferable that the two end points of the range for line analysis are not inside the particle, but on the outer periphery of the particle or in a place where no particle is present. It is more preferable that the range for line analysis crosses as long a portion of the particle as possible, and for example, when crossing the entirety of one particle, it is more preferable to cross the long axis of the particle (a line segment including two points on the outer periphery of the particle that are the longest distance). The count number is measured for each position having a length of about the atomic interplanar spacing or lattice constant. For example, the measurement point interval (position interval) is preferably 0.5 nm or less, more preferably 0.30 nm or less, and particularly preferably 0.25 nm or less. From the viewpoint of improving accuracy, it is preferable that the integrated count number of the characteristic X-ray peak is 400 or more. If the count is low, the standard deviation may be overestimated. When repeatedly scanning a specific area, the count number can be increased by increasing the number of measurements or the measurement time. Background counts vary from measurement to measurement. The background counts are calculated from the integrated counts in the portion of the sample where the element is not obviously present, to determine the background threshold. Assuming that each element is present at a position where the count number exceeds the background threshold, the proportion (composition) of each element at each position is calculated based on the count number. For the composition of positions with counts above the background threshold, the average composition and standard deviation are determined using the usual arithmetic mean. When the standard deviation of the distribution of each element in the alloy is calculated from the element map, 2D analysis may be performed. Pixels can be set in the STEM data. It is preferable to adjust the measurement point interval in 1D analysis (line analysis) and the pixel size in 2D analysis depending on the grain size of the alloy.

[0031] <Correlation coefficient of distribution> In the alloy of the present invention, from the viewpoint of preventing segregation, it is preferable that the correlation coefficient of the distribution of each of the two elements constituting the alloy is less than ±0.50, more preferably within ±0.45, and particularly preferably within ±0.40. In the alloy of the present invention, the correlation coefficient between the distributions of at least two types of two elements constituting the alloy is preferably less than ±0.50, more preferably within ±0.45, and particularly preferably within ±0.40. As the segregation of the distribution of elements in an alloy decreases, the correlation coefficient value of the distribution of each element changes from a state in which the elements are close (positive value, close to 1) or exclusive (negative value, close to 1) to a state in which there is almost no correlation (absolute value close to 0).

[0032] The calculation of the correlation coefficient for the composition can be applied to the analysis of alloys by applying the method used in the field of geology to evaluate the composition distribution of minerals (rocks). The correlation coefficient for the distribution of two elements that compose an alloy can be obtained by the following method. For details, refer to Jour. Geol. Soc. Japan (2006) Vol. 112, No.3, p.173-187, which is incorporated herein by reference. First, a centered logratio transformation (clr) is performed on the sample composition vectors of each measurement point, and a one-to-one coordinate transformation is performed from the composition space, whose values ​​are restricted to 0 to 1, to the real space (performing the coordinate transformation makes it possible to apply normal multivariate analysis to the composition vector sample data). The variance and covariance are calculated for the composition sample vectors after the coordinate transformation using the following formula, and the correlation coefficient is calculated. Centered log-ratio transformation: clr(vec_x)=(ln x_A / g(x), ln x_B / g(x), ln x_C / g(x)) = (z_A, z_B, z_C) Here, g(x)=(Πx_i) (1 / 3) (i=A,B,C) Multivariate analysis using the transformed vectors is the same as that in normal real space, and can be performed by known methods. Note that no inverse transformation is required for correlation coefficients, but the statistical values ​​calculated by subsequently performing the CLR inverse transformation are inversely mapped to the composition space to obtain the calculated values.

[0033] <Alloy shape> The shape of the alloy of the present invention may be a lump (bulk) or a particulate or particle aggregate (powder), and is not particularly limited. The alloy is preferably in the form of particulates (fine particles), and more preferably in the form of alloy nanoparticles. When the alloy of the present invention is in the form of particles or a particle aggregate (powder), each particle is in contact with the interface. Alloy nanoparticles refer to particles with an average particle size of less than 1000 nm. The alloy nanoparticles may have various shapes such as a sphere, an ellipsoid, a rectangular tube, a cylinder, a cube, a rectangular parallelepiped, or a scale, and are preferably spherical or ellipsoid. The average particle size of the alloy nanoparticles is preferably 0.5 to 50 nm, more preferably 0.5 to 30 nm, and further preferably 0.5 to 20 nm. The average particle size of the alloy nanoparticles can be calculated as an arithmetic mean by direct observation with, for example, a transmission electron microscope (TEM). The average particle size of the alloy nanoparticles is the average particle size of the alloy, and when the alloy nanoparticles are supported on a support, it is the average particle size of the alloy portion other than the support. The particle size distribution of the alloy nanoparticles is preferably within the average particle size ±0.1 to 15 nm, more preferably ±0.3 to 15 nm, and particularly preferably ±1.0 to 10 nm.

[0034] The alloy of the present invention may be in the form of an aggregate of alloy nanoparticles, or may be in the form of being supported on a carrier.

[0035] (Aggregation of alloy nanoparticles) The aggregate of alloy nanoparticles refers to a powder consisting of a large number of alloy nanoparticles. For example, it is preferable that the assembly of alloy nanoparticles does not substantially contain a carrier or the like, or is not supported on a carrier. The collection of alloy nanoparticles may include a protective agent, such as a polymer. Furthermore, the aggregate of alloy nanoparticles may have an oxide coating or the like on the surface of each alloy nanoparticle. The assembly of alloy nanoparticles may contain impurity particles in addition to the alloy (alloy nanoparticles) of the present invention, but the assembly of alloy nanoparticles preferably contains 90% by number or more of the alloy of the present invention, more preferably 98% by number or more, particularly preferably 99% by number or more, and even more particularly preferably 100% by number. The alloy nanoparticle aggregate may contain alloy nanoparticles in which all three or more elements contained in the compound used for production are solid-dissolved, as well as alloy nanoparticles in which only some of the three or more elements contained in the compound used for production are solid-dissolved. However, it is preferable that the proportion of alloy nanoparticles in which the same type of element is solid-dissolved is high. Of the alloy nanoparticles constituting the alloy nanoparticle aggregate, it is preferable that the alloy nanoparticles containing all three or more elements as constituent elements are 90% or more by number, more preferably 98% or more by number, particularly preferably 99% or more by number, and even more particularly preferably 100% by number. The ratio of each particle contained in the alloy nanoparticle aggregate is determined within a visual field in which a part of the alloy nanoparticle aggregate is observed. For example, it is preferable that the alloy nanoparticles constituting the alloy nanoparticle aggregate, which contain all of five or more elements as constituent elements, are contained within the above range within a certain visual field in which a part of the alloy nanoparticle aggregate is observed. However, it is more preferable to determine the ratio of each particle contained in the alloy nanoparticle aggregate as an average within a plurality of visual fields in which a part of the alloy nanoparticle aggregate is observed.

[0036] (Carrier) The carrier is not particularly limited. The support to be used is not particularly limited, but specific examples of the support include oxides, nitrides, carbides, elemental carbon, and elemental metals. Examples of oxides used for the support include oxides such as silica, alumina, ceria, titania, zirconia, and niobia, and composite oxides such as silica-alumina, titania-zirconia, ceria-zirconia, and strontium titanate. Examples of elemental carbon include activated carbon, carbon black, graphite, carbon nanotubes, and activated carbon fibers. The nitrides include boron nitride, silicon nitride, gallium nitride, indium nitride, aluminum nitride, zirconium nitride, vanadium nitride, tungsten nitride, molybdenum nitride, titanium nitride, and niobium nitride. The carbides include silicon carbide, gallium carbide, indium carbide, aluminum carbide, zirconium carbide, vanadium carbide, tungsten carbide, molybdenum carbide, titanium carbide, niobium carbide, and boron carbide. Examples of elemental metals include pure metals such as iron, copper, and aluminum, and alloys such as stainless steel. In the present invention, the support is preferably a non-carbon fiber support or a non-graphene support, more preferably a non-carbon material support (a material that is not made of elemental carbon) or a particulate carbon support, particularly preferably a non-carbon material support from the viewpoint that the support does not burn in a high-temperature oxidizing atmosphere, and more particularly preferably an oxide support. Activated carbon or the like can be used as the particulate carbon support.

[0037] <Protective agent> The solid solution of the present invention may be coated with a protective agent (preferably a surface protective agent). Examples of the protective agent include polymers such as polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG), amines such as oleylamine, and carboxylic acids such as oleic acid.

[0038] <Alloy manufacturing method> In the method for producing an alloy of the present invention, it is preferable to simultaneously reduce the metal ions contained in the mixed solution. There is no particular limitation on the method for simultaneously reducing the metal ions contained in the mixed solution, but the following method can be mentioned, for example. (1) A method in which solutions of compounds containing each element that makes up the alloy (raw material solutions) are ultrasonically treated individually and then mixed together. (2) In the case of rapid reactions in flow reactors, a method of keeping the temperature, flow rate, and pressure strictly constant from the start of adding chemicals (reducing agent solution, raw material solution, or a mixture of these) to the reaction system until completion. (3) In a spray system, a method for controlling the spray condition to a constant level. In the method for producing an alloy of the present invention, solutions of compounds containing each element constituting the alloy (raw material solutions) are individually ultrasonically treated and then mixed. It is preferable to mix the mixed solution with a reducing agent. It is more preferable to mix the mixed solution with a heated reducing agent that has sufficient reducing power. A preferred embodiment of the method for producing the alloy will now be described.

[0039] (Preparation of raw material solution) The method for producing the alloy preferably includes a step of individually preparing solutions of compounds (raw material solutions) containing each of the elements that make up the alloy. The elements that make up the alloy are dissolved in a solvent. Examples of polar solvents that can be used include water, alcohols (methanol, ethanol, isopropanol, etc.), polyols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, glycerin, etc.), polyethers (polyethylene glycol, etc.), acetonitrile, acetone, dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone, etc. Among these, water and alcohol are preferred. As the non-polar solvent, hexane, benzene, toluene, diethyl ether, chloroform, ethyl acetate, THF, etc. can be used. As the raw material solution, it is preferable to use an aqueous solution containing a water-soluble salt of a metal element or a water-soluble salt of an element other than a metal, but in the case of a combination of non-polar metal salts, a non-polar solvent containing a non-polar metal salt may be used. By adjusting the molar ratio of the compound containing each element, the molar ratio of each element in the resulting alloy can be adjusted.

[0040] Examples of water-soluble salts of elements include the following: Known water-soluble salts (e.g., sulfates, nitrates, acetates, chlorides, bromides, iodides, potassium cyanates, sodium cyanates, hydroxides, carbonates, etc.) of platinum group metals (Ru, Rh, Pd, Os, Ir, Pt), Ag, Au, Cd, Hg, In, Tl, Sn, Pb, Sb, Bi, Mo, W, Tc, Re, 3d metals (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), Ga, Ge, As, B, Al, C, Si, N, P, Y, Zr, Nb, lanthanides, Hf and Ta. In particular, the following are preferred: Ru: RuCl3, RuCl3·nH2O, RuBr3, K2RuCl5(NO), and other ruthenium halides, ruthenium nitrate, and Ru3(CO) 12 , Ru(NO)(NO3) a (OH) b , Ru(acac)3, etc. Rh: Rhodium acetate, rhodium nitrate, rhodium chloride (RhCl3), RhCl3·3H2O, etc. Pd: K2PdCl4, Na2PdCl4, K2PdBr4, Na2PdBr4, palladium nitrate, etc. Os: Osmium halides such as OsCl3, OsBr3, etc. Ir: iridium chloride, iridium acetylacetonate (acac; it is preferable to dissolve the acac system in a non-polar solvent), potassium iridium cyanate, potassium iridate, H2IrCl6, etc. Pt: K2PtCl4, (NH4)2K2PtCl4, (NH4)2PtCl6, Na2PtCl6, H2PtCl6, Pt(acac)2 etc. Au: AuCl3, HAuCl4, K[AuCl4], Na[AuCl4], K[Au(CN)2], K[Au(CN)4], AuBr3, HAuBr4, etc. Ag: AgNO3, Ag(CH3COO), etc. In: InCl3 4H2O, etc. Sn: SnCl3·2H2O, Sn(ethyhex)2, etc. Mo: Mo(CO)6, etc. Cu: Cu(NO3)2, CuSO4, Cu(CH3COO)2, CuCO3, CuCl, CuCl2, etc. Fe: FeCl3·6H2O, Fe(NO3)3, etc. B: BH3, etc. N: Ru(NO)(NO3) a (OH) b , ammonia, nitric acid, hydrazine, etc.

[0041] (Individual sonication) The method for producing an alloy preferably includes a step of ultrasonically treating solutions (raw material solutions) of compounds containing each of the elements constituting the alloy separately. By ultrasonically treating the raw material solutions separately, an alloy having significantly higher uniformity of solid solution can be obtained than when a solution containing all of the compounds containing each of the elements constituting the alloy is ultrasonically treated collectively. The ultrasonic treatment is preferably performed in the dark in order to suppress the reduction of the compounds containing each element due to light, and is preferably performed at a low temperature such as in an ice bath in order to suppress the reduction of the metal salt due to heat. The effect of individual ultrasonic treatments and the effects of light shielding and temperature during ultrasonic treatment may differ depending on the types of elements constituting the alloy, the type of raw material solution, etc. Therefore, the degree to which the uniformity of the solid solution is increased by these processes may differ depending on the types of elements constituting the alloy, the type of raw material solution, etc. However, as an alternative to the step of individually ultrasonically treating the raw material solutions, if there is a method capable of uniformly preparing individual raw material solutions at a speed equivalent to that achieved by individually ultrasonically treating the raw material solutions, that method may be used.

[0042] (Preparation of reducing agent) The method for producing the alloy preferably includes the step of preparing a reducing agent. The reducing agent is preferably a liquid reducing agent. Examples of liquid reducing agents include polyhydric alcohols such as ethylene glycol, glycerin, diethylene glycol, and triethylene glycol; lower alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol under high pressure; hydrous alcohols such as hydrous ethanol under high pressure; a THF solution of BH3 (THF complex); or a hydrazine or NaBH4 solution, a sodium naphthalenide solution, and the like. In addition, each element constituting the alloy may be used as a reducing agent. For example, a THF solution of BH3 (THF complex) may be used as a reducing agent to form an alloy containing the B element. When mixing and heating are performed under pressure using a flow device described later, a reducing agent with a low boiling point can be preferably used. The boiling point of the lower alcohol, which is a preferred reducing agent, is from room temperature to about 130°C, more preferably about 40 to 120°C, and even more preferably about 60 to 100°C. Since these reducing agents have a low boiling point under normal pressure, it is difficult to reduce compounds (metal compounds, etc.) containing each element constituting the alloy to form an alloy composed of metals that do not form a solid solution in the phase equilibrium diagram. By reacting at high temperature under pressure, they acquire reducing properties and can function as a reducing agent for obtaining an alloy composed of metals that do not form a solid solution in the phase equilibrium diagram. The reducing agent is used in an amount of at least one equivalent, preferably an excess amount, for reducing the compounds (preferably water-soluble salts) containing the elements constituting the alloy.

[0043] (mixture) The method for producing the alloy preferably includes a step of mixing the individual ultrasonically treated raw material solutions to form a mixed solution. It is preferable to mix a reducing agent into the raw material solution before or when the mixed solution is heated. The method for producing the alloy preferably includes a step of heating the mixed solution to cause a reaction. The reaction time during heating can be about 1 minute to 12 hours. The heating is preferably carried out with stirring. The reaction temperature during heating is preferably about 170 to 300° C., more preferably about 180 to 250° C. When a reducing agent such as NaBH4 is used, it may be used at room temperature or after cooling.

[0044] The method of mixing or heating is not particularly limited. For example, either or both of the reducing agent and the mixed solution may be heated before mixing. In addition, the method for producing an alloy preferably includes a step of heating the reducing agent, and the reducing agent heated in this step is preferably mixed with the raw material solution to cause a thermal reaction. For example, the reducing agent may be heated, and the mixed solution may be mixed by dropping it with a pump (syringe pump) or spraying it with a spray device. Alternatively, three or more types of raw material solutions that have been separately subjected to ultrasonic treatment and a solution of a reducing agent may be supplied to a reaction vessel, and mixed and heated using a flow device (flow reactor) that heats and reacts under pressure. When pressurizing with a flow device, the pressure of the raw material solution and the reducing agent solution is about 0.1 to 10 MPa, preferably about 0.2 to 9 MPa. The pressure inside the reaction vessel is about 0.1 to 10 MPa, preferably about 0.2 to 9 MPa. The temperature (reaction temperature) of the reaction vessel when pressurizing is about 100 to 500°C, preferably 150 to 400°C, more preferably about 180 to 300°C.

[0045] (Alloy separation) The method for producing the alloy preferably includes a step of separating and collecting a precipitate from the solution after the heating reaction. This process makes it possible to obtain an alloy containing three or more metals in a solid solution state. Methods for separating and isolating the precipitate include drying under reduced pressure, centrifugation, filtration, sedimentation, reprecipitation, and separation using a powder separator (cyclone). Before separating out the precipitate, it is preferable to allow the reaction solution to cool or to rapidly cool it.

[0046] By adding a protective agent to the mixed solution, the reducing agent, or a reaction solution in which these are mixed, it is possible to obtain particles (preferably alloy nanoparticles) in which aggregation is suppressed. When a protective agent is used, the protective agent is contained in a reaction solution obtained by mixing a mixture of the raw material solutions and a reducing agent at a concentration of preferably 0.01 to 100 times, more preferably 0.5 to 50 times, and even more preferably 1 to 10 times the total amount of metal compounds in terms of mass ratio. The protective agent may be contained in the raw material solution, the reducing agent, or both the raw material solution and the reducing agent.

[0047] Furthermore, by making a carrier coexist in the mixed solution, the reducing agent, or a reaction solution in which these are mixed, a supported catalyst in which the alloy is supported on the carrier can be obtained. By making the support coexist in the reaction solution, a supported catalyst in which the multi-element solid solution is supported on the support can be obtained. When the multi-element solid solution is in the form of fine particles, a supported catalyst in which aggregation of the fine particles is suppressed can be obtained by adding a protective agent simultaneously with the support to the reaction solution for producing the multi-element solid solution fine particles.

[0048] On the other hand, neither a protective agent nor a carrier may be added to the mixed solution, the reducing agent, or a reaction solution obtained by mixing these. In this way, an alloy that is an aggregate of alloy nanoparticles can be obtained. In this case, the alloy, which is an aggregate of alloy nanoparticles, and the support are mixed in a solution or the powders are mixed in a non-solvent system or a solvent system, and then molded to obtain a supported catalyst in which the alloy is supported on the support. When a solvent is used, the mixture may be filtered and then dried as necessary.

[0049] [catalyst] The alloy of the present invention can be used as a catalyst exhibiting excellent performance. There is no particular restriction on the form of the alloy when used as a catalyst. The catalyst may be used as a supported catalyst.

[0050] There is no particular limit to the catalytic reactions in which the alloy of the present invention exhibits excellent catalytic performance, and examples of such reactions include those known to use catalysts containing platinum group elements. Specific examples include chemical reactions such as reduction reactions including hydrogenation reactions, dehydrogenation reactions, oxidation reactions including combustion, and coupling reactions. In addition, by utilizing these catalytic performances, the alloy can be suitably used in various processes, devices, and other applications. There is no particular limit to the applications in which the alloy of the present invention can be suitably used, and examples of such applications include catalysts for hydrogen evolution reaction (HER), catalysts for hydrogenation reactions, catalysts for hydrogen oxidation reactions, catalysts for oxygen reduction reactions (ORR), catalysts for oxygen evolution reactions (OER), catalysts for nitrogen oxide (NOx) reduction reactions, catalysts for carbon monoxide (CO) oxidation reactions, catalysts for dehydrogenation reactions, catalysts for VVOC or VOC oxidation reactions, catalysts for exhaust gas purification, catalysts for water electrolysis reactions, and catalysts for hydrogen fuel cells. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.

[0052] [Device] In the examples, the following instruments were used. For PXRD, Rigaku Miniflex600 (Cu Kα) was used unless otherwise specified. (i-1)Powder X-ray Diffraction (PXRD) Rigaku Miniflex600 (Cu Kα) (i-2)PXRD SPring-8 BL02B2(λ=0.63Å, 0.58Å) (i-3)PXRD SPring-8 BL04B2 (ii) Energy-dispersive x-ray spectroscopy in scanning transmission electron microscopy (STEM-EDS) and EELS JEOL JEM-ARM200CF (accelerating voltage: 120 kV) (iii) X-ray fluorescence analysis (XRF) X-ray fluorescence analyzer ZSX Primus IV

[0053] [Example 1]: AuRuIr <Individual ultrasonic treatment of metal ion solutions> A metal ion solution prepared by dissolving HAuBr4 in diethylene glycol (DEG) was ultrasonically treated for 5 minutes in the dark. Unless otherwise specified, the ultrasonic treatment was carried out at low temperature with ice cooling. A metal ion solution prepared by dissolving K2RuCl5(NO) in diethylene glycol (DEG) was ultrasonically treated for 5 minutes in the dark. A metal ion solution prepared by dissolving H2IrCl6 in diethylene glycol (DEG) was ultrasonically treated for 5 minutes. The three types of metal ion solutions subjected to individual ultrasonic treatment were mixed at a ratio of 1:1:1, and each metal ion mixed solution of 0.15 mmol of DEG solution was dissolved together to about 3 ml and adjusted to 10 ml.

[0054] <Preparation of alloy> 100 ml of ethylene glycol (EG) containing polyvinylpyrrolidone (PVP) K30 (4 mmol; manufactured by Fujifilm Wako Pure Chemical Corporation) was heated and stirred at 195 °C. To this solution, the metal ion mixed solution was fed (dropped) at a rate of 1.5 ml / min with a syringe pump and added, and maintained at 195 °C for 10 minutes. Then, it was allowed to cool to room temperature. The resulting precipitate, the nanoparticles, were separated by centrifugation.

[0055] <Elemental analysis by STEM-EDS> The separated nanoparticles were subjected to STEM-EDS analysis. Elemental analysis was performed by line scan using multiple fields of view of a scanning transmission electron microscope, and the metal composition of the three elements was calculated. The analysis method of line analysis in each of the following examples and comparative examples describes actual data in which one or more particles were selected in the field of view of a specific measurement point and analyzed in the direction of the arrow, but almost the same results were obtained even if one or more other particles were arbitrarily selected and analyzed, and the same quality was obtained even if the direction of the arrow, the particle shape, and the particle size were different. Therefore, it is considered that almost the same results can be obtained for any alloy nanoparticle that constitutes an aggregate. At the measurement points in Figure 1, elemental analysis was performed every 0.15 to 0.30 nm at 100 points from the 0.00 nm position to the 25.90 nm position for the arrowed portion. The background threshold was set to 30 counts. The nanoparticles were counted from the 4.67 nm position to the 17.70 nm position, and the length of the nanoparticles on this arrowed portion was approximately 13.03 nm. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion of Figure 1 are shown in Figure 2(A) and Figure 2(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were determined at the measurement points in Figure 1, and are shown in Table 2 below. The average composition was determined using the usual arithmetic mean. Standard deviations were determined using the usual arithmetic mean. The correlation coefficient was calculated by performing centered log ratio transformation (clr). For the clr transformation, refer to Jour. Geol. Soc. Japan (2006) Vol. 112, No.3, pp. 173-187. Specifically, the EDX line analysis data was converted to composition data using the EDX measurement software Noran system 7 (manufactured by Thermo Fisher Scientific), and the correlation coefficient was calculated using the statistical calculation software R and the R library package Compositions. Compositions is a library for statistical analysis of composition data (see “Analyzing Compositional Data with R”, van den Boogaart, K. Gerald, Tolosana-Delgado, Raimon, Softcover ISBN:978-3-642-36808-0, published by Springer).

[0056] [Table 2]

[0057] At the measurement points in FIG. 3, elemental analysis was performed for the nanoparticles obtained in Example 1 at every 0.15 to 0.30 nm in the part indicated by the arrow. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the part indicated by the arrow in FIG. 2 are shown in FIG. 3(A) and FIG. 3(B), respectively. The average composition and the standard deviation of the distribution of each element constituting the alloy within the alloy were determined and are listed in Table 3 below. The average composition, standard deviation, and correlation coefficient were determined in the same manner as in Example 1.

[0058] [Table 3]

[0059] At the measurement points in Fig. 5, for the arrow parts, elemental analysis of the nanoparticles obtained in Example 1 was performed every 0.15 - 0.30 nm. The background threshold was set at 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrow part of Fig. 5 are shown in Fig. 6(A) and Fig. 6(B), respectively. The average composition and the standard deviation of the distribution of each element constituting the alloy within the alloy were determined and listed in Table 4 below. The average composition, standard deviation, and correlation coefficient were determined in the same manner as in Example 1.

[0060]

Table 4

[0061] From Tables 2 - 4, it was found that the alloys of the present invention have high solid solution uniformity in the shape of the nanoparticles.

[0062] In addition, HAADF-STEM images and EDS maps of a part of all the obtained alloys are shown in Fig. 7. From Fig. 7, as far as observed in the STEM images, it was confirmed that all the elements were solid-solved in each nanoparticle. That is, within the range of the field of view confirmed in this example, it can be seen that the aggregate of alloy nanoparticles contains 100% of alloy nanoparticles in which all three elements contained in the compound used for production as constituent elements are solid-solved. Also, it can be seen that any alloy nanoparticle constituting the aggregate of the alloys of the present invention contains all three elements contained in the compound used for production as constituent elements.

[0063] <XRD Analysis> For the obtained AuRuIr nanoparticles, XRD analysis was performed using SPring-8 BL02B2. The obtained results are shown in Fig. 8.

[0064] <Analysis by TEM> A TEM photograph of the obtained AuRuIr nanoparticles is shown in Fig. 9. From Fig. 9, the average particle size of the obtained nanoparticles was 8.9 ± 1.7 nm.

[0065] <Manufacture of Electrodes> The nanoparticles of AuRuIr obtained were supported on carbon particles to produce an electrode catalyst (alloy / C: metal amount 20 wt%). The nanoparticles were 0.05 mg in weight. The synthesized alloy nanoparticles were mixed with carbon particles (Vulcan-XC-72R) in water at a ratio of 20 wt%, supported on carbon by ultrasonic dispersion, collected by centrifugation, and dried to produce a catalyst powder. 2.5 mg of this catalyst powder was dispersed in a mixed solution of 6.55 ml of isopropanol and 3.44 ml of water, and 0.01 ml of 5 wt% Nafion (registered trademark) solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added and thoroughly mixed to prepare a catalyst ink. A suitable amount of this ink was applied to a working electrode such as a rotating ring disk electrode or a glassy carbon electrode to produce a catalyst electrode.

[0066] <Catalytic activity> Current measuring device: Potentiostat (BAS ALS760E) Measurement method: A rotating ring-disk electrode with the obtained AuRuIr nanoparticles supported on carbon particles was used as the cathode, and a three-electrode cell (counter electrode: platinum wire, reference electrode: silver-silver chloride electrode (Ag / AgCl), electrolyte: 0.1 M HClO4 aqueous solution, 25°C, oxygen saturated) was used to measure the current value I when the potential E was swept from 0.1 V to -0.4 V (vs. RHE) at 5 mV / s, and the HER catalytic activity was evaluated three times. The results are shown in Figure 10(A) and Figure 10(B).

number

[0067] [Example 11]: RuRhAu <Individual sonication of metal ion solutions> A metal ion solution was prepared by dissolving HAuBr4 in diethylene glycol DEG, and was sonicated for 5 minutes in the dark. A metal ion solution was prepared by dissolving K2RuCl5(NO) in diethylene glycol DEG and ultrasonicated for 5 minutes in the dark. A metal ion solution was prepared by dissolving RhCl3 in diethylene glycol (DEG) and ultrasonicated for 5 minutes. The three types of metal ion solutions that had been individually sonicated were mixed in a 1:1:1 ratio, and each metal ion mixed solution of 0.15 mmol of DEG solution was dissolved in approximately 3 ml of the solution to prepare a total volume of 10 ml.

[0068] <Alloy preparation> 100 ml of ethylene glycol (EG) containing polyvinylpyrrolidone (PVP) K30 (4 mmol; Fujifilm Wako Pure Chemical Industries, Ltd.) was heated and stirred at 195°C. The metal ion mixed solution was added to this solution by dripping at a rate of 1.5 ml / min using a syringe pump, and the solution was maintained at 195°C for 10 minutes. It was then allowed to cool to room temperature. The resulting precipitate, which was nanoparticles, was separated by centrifugation.

[0069] <Elemental analysis> The separated nanoparticles were analyzed by STEM-EDS. Elemental analysis was performed by line scan analysis using multiple fields of view of a scanning transmission electron microscope, and the metal composition of the three elements was calculated. At the measurement points in Figure 11, elemental analysis was performed every 0.10 to 0.20 nm at 120 points from the 0.00 nm position to the 19.20 nm position for the arrowed portion. The background threshold was set to 35 counts. The nanoparticles were counted from the 3.86 nm position to the 13.40 nm position, and the length of the nanoparticles on this arrowed portion was approximately 9.54 nm. Graphs of the count number and composition at each position in the arrowed portion of Figure 11 are shown in Figures 12(A) and 12(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of the two elements constituting the alloy at the measurement points in Figure 11 were determined in the same manner as in Example 1, and are listed in Table 5 below.

[0070] [Table 5]

[0071] At the measurement points in FIG. 13, elemental analysis was performed for the nanoparticles obtained in Example 11 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion in FIG. 13 are shown in FIG. 14(A) and FIG. 14(B), respectively. The average composition and the standard deviation of the distribution of each element constituting the alloy within the alloy were calculated and are shown in Table 6 below. The average composition, standard deviation, and correlation coefficient were calculated in the same manner as in Example 1.

[0072] [Table 6]

[0073] At the measurement points in FIG. 15, elemental analysis was performed on the nanoparticles obtained in Example 11 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion in FIG. 15 are shown in FIG. 16(A) and FIG. 16(B), respectively. The average composition and the standard deviation of the distribution of each element constituting the alloy within the alloy were calculated and are listed in Table 7 below. The average composition, standard deviation, and correlation coefficient were calculated in the same manner as in Example 1.

[0074] [Table 7]

[0075] At the measurement points in FIG. 17, elemental analysis was performed for the nanoparticles obtained in Example 11 at every 0.15 to 0.30 nm for the part indicated by the arrow. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the part indicated by the arrow in FIG. 17 are shown in FIG. 18(A) and FIG. 18(B), respectively. The average composition and the standard deviation of the distribution of each element constituting the alloy within the alloy were calculated and are shown in Table 8 below. The average composition, standard deviation, and correlation coefficient were calculated in the same manner as in Example 1.

[0076] [Table 8]

[0077] From Tables 5 to 8, it was found that the alloys of the present invention have high uniformity of solid solution in the shape of nanoparticles.

[0078] In addition, HAADF-STEM images and EDS maps of a part of all the obtained alloys are shown in Fig. 19. From Fig. 19, as long as observed in the STEM image, it was confirmed that all elements are solid-solved in each nanoparticle. That is, within the range of the visual field confirmed in this example, it can be seen that the aggregate of alloy nanoparticles contains 100% by number of alloy nanoparticles in which all three elements contained in the compound used for production as constituent elements are solid-solved. Also, it can be seen that any alloy nanoparticle constituting the aggregate of the alloys of the present invention contains all three elements contained in the compound used for production as constituent elements.

[0079] <XRD analysis> XRD analysis was performed on the obtained RuRhAu nanoparticles using SPring-8 BL02B2. The obtained results are shown in Fig. 20.

[0080] <Elemental analysis by TEM and XRF> A TEM photograph of the obtained RuRhAu nanoparticles is shown in Fig. 21. From Fig. 21, the average particle size of the obtained nanoparticles was 11.1 ± 2.5 nm. Elemental analysis was performed by XRF. As a result, Ru:Rh:Au = 35.1 atomic%: 34.3 atomic%: 30.6 atomic%.

[0081] <Catalytic activity> An electrode catalyst (alloy / C: metal amount 20 wt%) in which the obtained RuRhAu nanoparticles were supported on carbon particles was produced. The amount of nanoparticles was 0.05 mg. Electrodes were produced in the same manner as in Example 1. Current measuring device: Potentiostat (ALS760E manufactured by BAS) Measurement method: A rotating ring-disk electrode with the obtained RuRhAu nanoparticles supported on carbon particles was used as the cathode, and a three-electrode cell (counter electrode: platinum wire, reference electrode: silver-silver chloride electrode (Ag / AgCl), electrolyte: 0.1 M HClO4 aqueous solution, 25°C, oxygen saturated) was used to measure the current value I when the potential E was swept from 0.1 V to -0.4 V (vs. RHE) at 5 mV / s, to evaluate the HER catalytic activity. The results are shown in Figure 22(A) and Figure 22(B).

[0082] [Example 21]: fcc-PtIrRu <Individual sonication of metal ion solutions> A metal ion solution was prepared by dissolving K2RuCl5(NO) in ion-exchanged water, and was subjected to ultrasonic treatment for 5 minutes in the dark. A metal ion solution was prepared by dissolving H2PtCl6 in ion-exchanged water and subjected to ultrasonic treatment for 5 minutes. A metal ion solution was prepared by dissolving H2IrCl6 in ion-exchanged water and subjected to ultrasonic treatment for 5 minutes. The three metal ion solutions, which had been individually sonicated, were mixed in a ratio of H2PtCl6:K2RuCl5(NO):H2IrCl6 = 1.5:7:1.5, and 0.2 mmol of each metal ion mixed solution was dissolved in water to prepare a 20 ml solution.

[0083] <Alloy preparation> 100 ml of ethylene glycol (EG) containing polyvinylpyrrolidone (PVP) K30 (4 mmol; Fujifilm Wako Pure Chemical Industries, Ltd.) was heated and stirred at 190°C. The metal ion mixed solution was added to this solution by spraying, and the mixture was maintained at 190°C for 10 minutes. The mixture was then allowed to cool to room temperature. The resulting precipitate, which was nanoparticles, was separated by centrifugation to prepare the alloy of Example 21, which was nanoparticles.

[0084] [Example 22]: hcp-PtIrRu <Individual sonication of metal ion solutions> A metal ion solution was prepared by dissolving K2RuCl5(NO) in diethylene glycol (DEG), and sonicated for 5 minutes in the dark. A metal ion solution was prepared by dissolving Pt(acac)2 in diethylene glycol (DEG), and sonicated for 5 minutes. A metal ion solution was prepared by dissolving H2IrCl6 in diethylene glycol (DEG), and sonicated for 5 minutes. The three individually sonicated metal ion solutions were mixed at Pt(acac)2:K2RuCl5(NO):H2IrCl6 = 1.5:7:1.5 to prepare a metal ion mixed solution of 0.2 mmol of diethylene glycol (DEG) solution (10 ml).

[0085] <Preparation of alloy> 100 ml of ethylene glycol (EG) containing polyvinylpyrrolidone (PVP) K30 (0.6 mmol; manufactured by Fujifilm Wako Pure Chemical Corporation) was heated and stirred at 180 °C. To this solution, the metal ion mixed solution was fed (dropped) at a rate of 3.0 ml / min with a syringe pump and added, and then rapidly cooled to room temperature. The resulting precipitate, the nanoparticles, were separated by centrifugation to prepare the alloy of Example 22 which is nanoparticles.

[0086] <Elemental analysis by STEM-EDS> The STEM-EDS analysis of the separated alloy of Example 21 and the alloy of Example 22 was performed in the same manner as in Example 1. First, for the alloy (fcc-PtIrRu) nanoparticles obtained in Example 21, elemental analysis was performed by line scan using multiple fields of a scanning transmission electron microscope to calculate the metal composition of the three elements. At the measurement points in FIG. 23, elemental analysis was performed for the nanoparticles obtained in Example 21 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion in FIG. 23 are shown in FIG. 24(A) and FIG. 24(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were calculated and are listed in Table 9 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0087] [Table 9]

[0088] At the measurement points in FIG. 25, elemental analysis was performed for the nanoparticles obtained in Example 21 at every 0.15 to 0.30 nm for the part indicated by the arrow. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the part indicated by the arrow in FIG. 25 are shown in FIG. 26(A) and FIG. 26(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were calculated and are shown in Table 10 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0089] [Table 10]

[0090] At the measurement points in FIG. 27, elemental analysis was performed on the nanoparticles obtained in Example 21 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion in FIG. 27 are shown in FIG. 28(A) and FIG. 28(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were calculated and are shown in Table 11 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0091] [Table 11]

[0092] From Tables 9 to 11, it can be seen that the alloy (fcc-PtIrRu) nanoparticles obtained in Example 21, which are the alloy of the present invention, have high uniformity of solid solution in the shape of the nanoparticles.

[0093] Next, the alloy (hcp-PtIrRu) nanoparticles obtained in Example 22 were subjected to elemental analysis by line scan analysis using multiple fields of view of a scanning transmission electron microscope, and the metal composition of the three elements was calculated. At the measurement points in FIG. 29, elemental analysis was performed for the nanoparticles obtained in Example 22 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion of FIG. 29 are shown in FIG. 30(A) and FIG. 30(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were calculated and are listed in Table 12 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0094] [Table 12]

[0095] At the measurement points in FIG. 31, elemental analysis was performed on the nanoparticles obtained in Example 22 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion in FIG. 31 are shown in FIG. 32(A) and FIG. 32(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were calculated and are listed in Table 13 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0096]

Table 13

[0097] From Tables 12 and 13, it can be seen that the alloy of the present invention, which is the alloy (Hcp-PtIrRu) nanoparticles obtained in Example 22, has high homogeneity of solid solution in the shape of the nanoparticles.

[0098] In addition, partial HAADF-STEM images and EDS maps of all the alloys (fcc-PtIrRu) obtained in Example 21 are shown in Fig. 33. Partial HAADF-STEM images and EDS maps of all the alloys (hcp-PtIrRu) obtained in Example 22 are shown in Fig. 34. From Figs. 33 and 34, as long as observed in the STEM images, it was confirmed that all the elements were dissolved in each nanoparticle. That is, within the range of the field of view confirmed in this example, it can be seen that the aggregate of alloy nanoparticles contains 100% by number of alloy nanoparticles in which all three elements contained in the compound used in the production as constituent elements are dissolved. Also, it can be seen that any alloy nanoparticle constituting the aggregate of the alloy of the present invention contains all three elements contained in the compound used in the production as constituent elements.

[0099] <XRD Analysis> XRD analysis was performed on the obtained alloys of Example 21 and Example 22. The obtained results are shown in Fig. 35.

[0100] <Elemental Analysis by TEM and XRF> The TEM photograph of the nanoparticles of the obtained alloy (fcc-PtIrRu) of Example 21 is shown in Fig. 36(A). From Fig. 36(A), the average particle size of the obtained nanoparticles was 3.5 ± 0.56 nm. Also, the TEM photograph of the nanoparticles of the alloy (hcp-PtIrRu) of Example 22 is shown in Fig. 36(B). From Fig. 36(B), the average particle size of the obtained nanoparticles was 3.0 ± 0.34 nm. Elemental analysis was performed using XRF. As a result, the alloy (fcc-PtIrRu) of Example 21 had a Pt:Ru:Ir ratio of 14.3 atomic %:71.4 atomic %:14.35 atomic %. The alloy (fcc-PtIrRu) of Example 22 had a Pt:Ru:Ir ratio of 14.7 atomic %:70.1 atomic %:15.2 atomic %.

[0101] <Catalytic activity> An electrode catalyst (alloy / C: metal amount 20 wt%) was produced in which the obtained nanoparticles of the alloy (fcc-PtIrRu) of Example 21 or the nanoparticles of the alloy (hcp-PtIrRu) of Example 22 were supported on carbon particles. The amount of nanoparticles was 10 μg. Current measuring device: Potentiostat (BAS ALS760E) Measurement method: A rotating ring-disk electrode with the obtained AuRuIr nanoparticles supported on carbon particles was used as the cathode, and a three-electrode cell (counter electrode: platinum wire, reference electrode: silver-silver chloride electrode (Ag / AgCl), electrolyte: 1 M KOH aqueous solution, 25°C, oxygen saturated) was used to measure the current value I when the potential E was swept from 0.00 V to -0.15 V (vs. RHE) at LSV 5 mV / s, and the HER catalytic activity was evaluated. The results are shown in Figure 37.

number

[0102] As shown in FIG. 37, the alloy of Example 22 (hcp-PtIrRu) exhibited better catalytic activity than the alloy of Example 22 (fcc-PtIrRu) and the commercially available Pt / C catalyst (Alfa Acer).

[0103] [Example 31]: PdRuB (1) Preparation of PdRu nanoparticles <Individual sonication of metal ion solutions> A metal ion solution was prepared by dissolving K2PdCl4 in ion-exchanged water, and was subjected to ultrasonic treatment for 5 minutes in the dark. A metal ion solution was prepared by dissolving K2RuCl5(NO) in ion-exchanged water and ultrasonically treated for 5 minutes in the dark. Two types of metal ion solutions treated with individual ultrasonic waves were mixed at K2PdCl4:K2RuCl5(NO)=1:1 to prepare a metal ion mixed solution of an aqueous solution (35 ml) containing 0.7 mmol of Pd and 0.85 mmol of Ru.

[0104] <Preparation of alloy> A triethylene glycol solution (150 ml) containing polyvinylpyrrolidone (PVP) K30 (0.6 mmol; manufactured by Fujifilm Wako Pure Chemical Corporation) was heated and stirred at 200 °C. The metal ion mixed solution was added by spraying to this solution, and then it was rapidly cooled to room temperature. The resulting precipitate, the nanoparticles, were separated by centrifugation to prepare PdRu nanoparticles.

[0105] (2) Preparation of PdRuB nanoparticles Using the obtained PdRu nanoparticles as raw materials, they were degassed at 80 °C overnight using a vacuum pump. Then, the system was purged with nitrogen gas. A 1 M THF solution of BH3 (manufactured by Sigma-Aldrich) was added in an excess amount to the PdRu nanoparticles and mixed, and it was heated and stirred at 80 °C for 2 days in a nitrogen atmosphere. The resulting precipitate, the nanoparticles, were separated by centrifugation to prepare PdRuB nanoparticles.

[0106] <Elemental analysis by STEM-EDS> The STEM-EDS analysis of the separated PdRuB nanoparticles was performed in the same manner as in Example 1. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of the two elements constituting the alloy were determined. It can be seen that the alloy of the present invention has high solid solution uniformity in the shape of the nanoparticles.

[0107] In addition, HAADF-STEM images and EDS maps of some of the obtained PdRuB nanoparticles are shown in Fig. 38, and HAADF-STEM images and EELS maps are shown in Fig. 39, respectively. From Figs. 38 and 39, it was confirmed that all elements were solid-solved in each nanoparticle as far as observed in the STEM images. That is, within the range of the visual field confirmed in this example, it can be seen that the aggregate of alloy nanoparticles contains 100% by number of alloy nanoparticles in which all three elements contained in the compound used for production as constituent elements are solid-solved. Also, it can be seen that in the alloy of the present invention, any alloy nanoparticle constituting the aggregate contains all three elements contained in the compound used for production as constituent elements.

[0108] <XRD Analysis> XRD analysis was performed on the obtained alloy of PdRuB nanoparticles using SPring-8 BL04B2. The obtained results are shown in Fig. 40.

[0109] <Elemental Analysis by TEM and XRF> A TEM photograph of the obtained PdRuB nanoparticles is shown in Fig. 41(A). From Fig. 41(A), the average particle size of the obtained nanoparticles was 12.9 ± 1.9 nm. In addition, a TEM photograph of the PdRu nanoparticles as intermediate products is shown in Fig. 41(B). From Fig. 41(B), the average particle size of the obtained nanoparticles was 12.9 ± 1.8 nm. Elemental analysis was performed by XRF. As a result, for the PdRu nanoparticles as intermediate products, Pd:Ru = 48 atomic%:52 atomic%.

[0110] [Example 41]: AuPdRu <Individual Ultrasonic Treatment of Metal Ion Solutions> A metal ion solution in which HAuCl4·3H2O was dissolved in ion-exchanged water was prepared and ultrasonically treated for 5 minutes in a light-shielded state. A metal ion solution in which K2PdCl4 was dissolved in ion-exchanged water was prepared and ultrasonically treated for 5 minutes in a light-shielded state. A metal ion solution was prepared by dissolving RuCl3·nH2O in ion-exchanged water and then ultrasonicated for 5 min in the dark. The three types of metal ion solutions that had been individually ultrasonicated were mixed in a 1:1:1 ratio, and each 0.35 mmol aqueous solution of the mixed metal ion solution was dissolved in approximately 13.3 ml of water to prepare a total volume of 40 ml.

[0111] <Alloy preparation> 300 ml of triethylene glycol (TEG) containing polyvinylpyrrolidone (PVP) K30 (10 mmol; Fujifilm Wako Pure Chemical Industries, Ltd.) was heated and stirred at 225°C. The metal ion mixture was added to this solution by spraying at a rate that did not cause the TEG solution to fall below 220°C, and the mixture was maintained at 225°C for 10 minutes. It was then allowed to cool to room temperature. The resulting precipitate, which was nanoparticles, was separated by centrifugation.

[0112] <Elemental analysis> The separated nanoparticles were subjected to STEM-EDS analysis. Elemental analysis was performed by line scan using multiple fields of view of a scanning transmission electron microscope, and the metal composition of the three elements was calculated. The uniformity of the solid solution is improved... At the measurement points in FIG. 42, elemental analysis was performed for the nanoparticles obtained in Example 41 at every 0.15 to 0.30 nm for the part indicated by the arrow. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the part indicated by the arrow in FIG. 42 are shown in FIG. 43(A) and FIG. 43(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy in the alloy, and the correlation coefficient of the distribution of the two elements constituting the alloy were calculated and are listed in Table 14 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0113] [Table 14]

[0114] From Table 14, it is clear that the alloy of the present invention has high uniformity of solid solution in the shape of nanoparticles.

[0115] [Comparative example 42]:AuPdRu <Alloy preparation> A metal ion solution was prepared by dissolving HAuCl4·3H2O in ion-exchanged water. A metal ion solution was prepared by dissolving K2PdCl4 in ion-exchanged water. A metal ion solution was prepared by dissolving RuCl3·nH2O in ion-exchanged water. Three metal ion solutions that had not been individually sonicated were mixed in a 1:1:1 ratio. A 0.35 mmol solution of each metal ion mixture was dissolved in approximately 13.3 ml of water to prepare a total volume of 40 ml.

[0116] Polyvinylpyrrolidone (PVP) K30 (4 mmol; Fujifilm Wako Pure Chemical Industries, Ltd.) in 300 ml of triethylene glycol (TEG) was heated and stirred at 225°C. The metal ion mixture was added to this solution by spraying at a rate that did not cause the TEG solution to fall below 220°C, and the mixture was maintained at 225°C for 10 minutes. It was then allowed to cool to room temperature. The resulting precipitate, which was nanoparticles, was separated by centrifugation.

[0117] <Elemental analysis> The separated nanoparticles were analyzed by STEM-EDS. Elemental analysis was performed by line scan analysis using multiple fields of view of a scanning transmission electron microscope, and the metal composition of the three elements was calculated. At the measurement points in FIG. 44, elemental analysis was performed for the nanoparticles obtained in Comparative Example 42 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion in FIG. 44 are shown in FIG. 45(A) and FIG. 45(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of the two elements constituting the alloy were calculated and are listed in Table 15 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0118] [Table 15]

[0119] At the measurement points in FIG. 46, elemental analysis was performed for the nanoparticles obtained in Comparative Example 42 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion of FIG. 46 are shown in FIG. 47(A) and FIG. 47(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were calculated and are listed in Table 16 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0120] [Table 16]

[0121] From Tables 15 and 16, it was found that the alloy of Comparative Example 42 had a standard deviation of distribution of each element (Ru) constituting the alloy within the alloy of 19% to 23%, which exceeds 15%, and the uniformity of the solid solution in the shape of the nanoparticles was low.

[0122] [Example 51]: RuRhPdOsIrPt <Individual sonication of metal ion solutions> A metal ion solution was prepared by dissolving K2PdCl4 in an ion-exchanged aqueous solution, and was subjected to ultrasonic treatment for 5 minutes in the dark. A metal ion solution was prepared by dissolving RuCl3·nH2O in an ion-exchange aqueous solution, and then ultrasonicated for 5 min in the dark. A metal ion solution was prepared by dissolving RhCl3·3H2O in an ion exchange aqueous solution and then ultrasonicated for 5 min in the dark. Metal ion solutions were prepared by dissolving OsCl3·3H2O in an ion-exchange aqueous solution and then ultrasonicated for 5 min in the dark. A metal ion solution was prepared by dissolving IrCl4·xH2O in an ion-exchanged aqueous solution, and then ultrasonicated for 5 min in the dark. A metal ion solution was prepared by dissolving K2[PtCl4] in an ion-exchange aqueous solution, and was subjected to ultrasonic treatment for 5 minutes in the dark. Six types of metal ion solutions that had been individually sonicated were mixed in a ratio of 1:1:1:1:1:1, and each metal ion mixed solution of 0.167 mmol of TEG solution was dissolved in approximately 1.5 ml to prepare a total volume of 10 ml.

[0123] <Alloy preparation> 100 ml of triethylene glycol TEG containing polyvinylpyrrolidone (PVP) K30 (4 mmol; Fujifilm Wako Pure Chemical Industries, Ltd.) was heated and stirred at 230°C. The metal ion mixed solution was added to this solution by dripping at a rate of 1.5 ml / min using a syringe pump, and the solution was maintained at 230°C for 10 minutes. It was then allowed to cool to room temperature. The resulting precipitate, which was nanoparticles, was separated by centrifugation.

[0124] <Elemental analysis> The separated nanoparticles were analyzed by STEM-EDS. Elemental analysis was performed by line scan analysis using multiple fields of view of a scanning transmission electron microscope, and the metal composition of six elements was calculated. At the measurement points in FIG. 48, elemental analysis was performed for the nanoparticles obtained in Example 51 at every 0.15 to 0.30 nm for the arrowed portion. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the arrowed portion of FIG. 48 are shown in FIG. 49(A) and FIG. 49(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were calculated and are shown in Tables 17 and 18 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0125] [Table 17]

[0126] [Table 18]

[0127] From Tables 17 and 18, it is clear that the alloy of the present invention has high uniformity of solid solution in the shape of nanoparticles.

[0128] [Example 61]: PdRuIrPtRh <Individual sonication of metal ion solutions> A metal ion solution was prepared by dissolving K2PdCl4 in an ion-exchanged aqueous solution, and was subjected to ultrasonic treatment for 5 minutes in the dark. A metal ion solution was prepared by dissolving RuCl3·nH2O in an ion-exchange aqueous solution, and then ultrasonicated for 5 min in the dark. A metal ion solution was prepared by dissolving RhCl3·3H2O in an ion exchange aqueous solution and then ultrasonicated for 5 min in the dark. A metal ion solution was prepared by dissolving IrCl4·xH2O in an ion-exchanged aqueous solution, and then ultrasonicated for 5 min in the dark. A metal ion solution was prepared by dissolving K2[PtCl4] in an ion-exchange aqueous solution, and was subjected to ultrasonic treatment for 5 minutes in the dark. The five metal ion solutions that had been individually sonicated were mixed in a ratio of 1:1:1:1:1, and each metal ion mixed solution of 0.200 mmol of TEG solution was dissolved in approximately 2.0 ml to prepare a total volume of 10 ml.

[0129] <Alloy preparation> 100 ml of triethylene glycol TEG containing polyvinylpyrrolidone (PVP) K30 (4 mmol; Fujifilm Wako Pure Chemical Industries, Ltd.) was heated and stirred at 230°C. The metal ion mixed solution was added to this solution by dripping at a rate of 1.5 ml / min using a syringe pump, and the solution was maintained at 230°C for 10 minutes. It was then allowed to cool to room temperature. The resulting precipitate, which was nanoparticles, was separated by centrifugation.

[0130] <Elemental analysis> The separated nanoparticles were analyzed by STEM-EDS. Elemental analysis was performed by line scan analysis using multiple fields of view of a scanning transmission electron microscope, and the metal composition of five elements was calculated. At the measurement points in FIG. 50, elemental analysis was performed for the nanoparticles obtained in Example 61 at every 0.15 to 0.30 nm for the part indicated by the arrow. The background threshold was set to 30 counts. Graphs of the characteristic X-ray counts and composition at each position in the part indicated by the arrow in FIG. 50 are shown in FIG. 51(A) and FIG. 51(B), respectively. The average composition, the standard deviation of the distribution of each element constituting the alloy within the alloy, and the correlation coefficient of the distribution of two elements constituting the alloy were calculated and are shown in Tables 19 and 20 below. The average composition, the standard deviation, and the correlation coefficient were calculated in the same manner as in Example 1.

[0131] [Table 19]

[0132] [Table 20]

[0133] From Tables 19 and 20, it can be seen that the alloy of the present invention has high uniformity of solid solution in the shape of nanoparticles.

Claims

1. An alloy composed of three or more elements, An alloy, wherein the standard deviation of the distribution of each of the elements constituting the alloy within the alloy is 15 atomic % or less.

2. The alloy according to claim 1, wherein the correlation coefficients of the distributions of the two elements constituting the alloy are both within ±0.

50.

3. The alloy according to claim 1 or 2, wherein the elements constituting the alloy include a combination of elements that are not solid-soluble in a phase equilibrium diagram.

4. The alloy according to any one of claims 1 to 3, wherein the elements constituting the alloy include at least three of the group consisting of platinum group (Ru, Rh, Pd, Os, Ir, Pt), Ag, Au, Cd, Hg, In, Tl, Sn, Pb, Sb, Bi, Mo, W, Tc, Re, 3d metals (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), Ga, Ge, As, H, B, Al, C, Si, N, P, Y, Zr, Nb, lanthanides, Hf and Ta.

5. The alloy according to any one of claims 1 to 4, wherein the elements constituting the alloy include at least one selected from the group consisting of Ru, Rh, Pd, Os, Ir, Pt, Ag, Au, and Ni.

6. The alloy contains m elements, m being an integer of 3 or more, For each element i constituting the alloy, where i is an integer of 1 or more and m or less, the average composition in the alloy is C i In the case of atomic percent, The standard deviation of the distribution of each element in the alloy is expressed by the following formula 1: i Using 2.5 × s i The alloy according to any one of claims 1 to 5, wherein the content of ZnO is 100 atomic % or less. [0010] (In formula 1, s i is the measured microvolume of 1 nm 3 represents the standard deviation for each element i in the composition distribution in the 3 It represents the number of atoms per unit.)

7. The alloy according to any one of claims 1 to 6, wherein the standard deviation of the distribution of each element constituting the alloy within the alloy is 40% or less of the composition ratio of the element within the alloy.

8. The alloy according to any one of claims 1 to 7, which is in the form of nanoparticles having an average particle size of 0.5 to 30 nm.

9. The alloy of claim 8 which is a collection of said nanoparticles.

10. The alloy of claim 8 , wherein the nanoparticles are supported on a carrier.

11. 11. The alloy of claim 10, wherein the support is a non-carbon material support or a particulate carbon support.

12. An aggregate of alloy nanoparticles, comprising 98% by number or more of the alloy according to claim 8.

13. A catalyst comprising the alloy according to any one of claims 1 to 11 or an aggregate of alloy nanoparticles according to claim 12.

Citation Information

Patent Citations

  • Multicomponent solid solution microparticles and method for producing same, and catalyst

    WO2017150596A1